An improved explicit time-marching procedure with b-spline interpolation and weighted residual technique for structural seismic response analysis. (1st December 2022) - Liu, Tianhao; Wen, Weibin
Highlights: An efficient B-spline based method is generalized for seismic response analysis. A general formulation of single-step and sub-step methods for seismic response is proposed. New method shows higher efficiency than other classical methods for seismic response analysis. Abstract: In this work, an improved calculation procedure based on an explicit time integration method is formulated for structural seismic response analysis. The mathematical derivation and unified calculation procedure based on b-spline interpolation and weighted residual technique are given for seismic response analysis. The calculation procedure is improved for Bouc-Wen hysteresis nonlinear system. The explicit method has desirable algorithm properties including stability and accuracy properties. The stability interval of the proposed method is smaller than that of the composite method proposed by Noh and Bathe. The numerical examples illustrate the proposed method can achieve much high accuracy and efficiency compared with the competitive methods.